Experience of Menarche Among Jordanian Adolescent Girls: An Interpretive Phenomenological Analysis - Al Omari, Omar; Abdel Razeq, N.; Fooladi, M. (2016)
Study Objective: Menarche is a significant physical and emotional experience for adolescent girls, especially in certain cultures, where it is viewed as a rite of passage, affecting the meaning of lived experiences. The purpose of the study was to explore the menarche experience among Jordanian adolescent girls when they reach menarche. Design: Interpretive phenomenological analysis. Setting: Az-Zarqa City, Jordan. Participants, Interventions, and Main Outcome Measures: A homogenous sample of 7 Jordanian girls, ages 12-14 years, who had their first menstruation within the past 6 months. Participants were asked to narrate their experiences through journal writing; their reports to be used for interpretive phenomenological analyses by 2 independent researchers, to ensure the findings' trustworthiness. Results: Three major themes emerged as: (1) menstruation as a forbidden topic; (2) keeping the "topic" to oneself; and (3) no more secrets. Each theme was characterized according to distinct sets of emotions and knowledge-seeking patterns because Jordanian culture and Islamic teachings had greatly influenced the girls' experience of menarche. Menarche was considered a social taboo; not to be openly discussed. At the first signs of menarche, participants were shocked, scared, confused, and anxious. They had limited information and support from their family or school system. Therefore, they relied on self-perceptions about menarche, and viewed the experience of menstruation with profound negative emotions. Participants hesitated to share their experiences with their mothers and close friends. They felt alone and experienced their emotional turmoil in isolation and without support. Conclusion: Jordanian adolescent girls need formal health education to understand and manage the reproductive changes that occur in their bodies.